Effects of nilotinib on platelet function in patients with chronic myeloid leukemia in chronic phase. (2019) - Alqasim, Alauldeen Mudhafar Zubair; Obaid, Ghasaq Mohsin; Yaseen, Yusra Ghaith; Alwan, Alaa Fadhil
Abstract: Background: Tyrosine kinases are highly expressed in platelets and play an important role in their activation process. Some studies have reported the blocking effects of tyrosine kinase inhibitors on different platelet functions. Objectives: Evaluate the effects of nilotinib on platelets aggregation in 42 patients with chronic phase of CML and correlate the results with clinical and hematological parameters: age, complete blood count and presentation. Patients and methods: This study was conducted on 42 patients diagnosed as Chronic Phase of Chronic Myeloid Leukemia based on clinical, morphological and cytogenetic study. All patients were on Nilotinib treatment and were attending the National Center of Hematology in Baghdad. About 9 mL of venous blood sample were collected from each patient and control subjects, samples divided into 3 parts for complete blood count, platelet aggregation test and PT and aPTT. Results: The mean age was 41.3 ± 1.7 (mean ± SEM) years old. M:F ratio of 1.2:1. Mean duration of nilotinib therapy(1.4 years). All patients had normal PT and aPTT. Only 16 (38%) patients had abnormal aggregation response to epinephrine, but there was no statistically significant differences with control group. Conclusion: Nilotinib had no adverse effect on platelet function nor patients clotting tests.